Nosocomial Infections from Intravenous Catheter - Rachma F. Boedjang (Paediatrica Indonesiana, 1995)
The subjects of the study consisted of 164 sick newborn infants (97 boys and 67 girls) who had no signs or symptoms of infections. The intravenous fluid drip (at scalp vein or saphenous vein) was put on soon after taking blood culture. Removal of venous catheters was indicated when the patients condition. No longer needed their use or there was sign of local infection. This study showed that the lower the birth weight or the gestational age, the higher the incidence of infection. The most prominent nosocomial infection in this study was phlebitis (16.5%) followed by infiltration (14.6%), and bacteremia (7 ,9%). The predominant microorganism was E. coli (59.7%). The overall incidence of nosocomial infection was 44.5% and the mortality was 24.7%.